VE-Cadherin and Vesicles Differentially Regulate Lymphatic Vascular Permeability to Solutes of Various Sizes - Jannaway, Melanie; Scallan, Joshua P. (Frontiers in Physiology, 2021)
Lymphatic vascular permeability prevents lymph leakage that is associated with lymphedema, lymphatic malformations, obesity, and inflammation. However, the molecular control of lymphatic permeability remains poorly understood. Recent studies have suggested that adherens junctions and vesicle transport may be involved in regulating lymphatic vessel permeability. To determine the contribution of each transport pathway, we utilized an ex vivo permeability assay to directly measure the solute flux of various molecular weight solutes across a range of pressures in intact murine collecting lymphatic vessels. Pharmacological and biological tools were used to probe the relative contributions of vesicles and junction proteins in the lymphatic vasculature. We show that the permeability of collecting lymphatic vessels is inversely related to the solute molecular weight. Further, our data reveal that vesicles selectively transport BSA, as an inhibitor of vesicle formation significantly decreased the permeability to BSA ( 60% decrease, n=8, P=0.02), but not to 3 kDa dextran (n=7, P=0.41), -lactalbumin (n=5, P=0.26) or 70 kDa dextran (n=8, P=0.13). In contrast, disruption of VE-cadherin binding with a function blocking antibody significantly increased lymphatic vessel permeability to both 3 kDa dextran (5.7-fold increase, n=5, P<0.0001) and BSA (5.8-fold increase, n=5, P<0.0001). Thus, in the lymphatic vasculature, adherens junctions did not exhibit selectivity for any of the solutes tested here, whereas vesicles specifically transport BSA. Overall, the findings suggest that disease states that disrupt VE-cadherin localization or expression will cause significant leakage of solutes and fluid from the lymphatic vasculature.